Implementasi Analisis Kebutuhan Diklat (AKD) dalam Rangka Pengembangan Kompetensi Aparatur Sipil (Studi pada Badan Kepegawaian Daerah Kota Batu) - Arihasmiramadan, Hayyu Lucky (Jurnal Administrasi Publik, 2016)
Abstract: Implementation of Training Needs Analysis (AKD) in the Framework of Civil Administrative Competence Development. Training Needs Analysis is organizing a program of activities which is closely related to the planning of education and training. Stone City Government through BKD Batu AKD implement programs with the aim of training can be achieved with the implementation of effective and targeted. Target on the successful implementation of education and training is a success parameter for realizing a competent personnel resources. Training Needs Analysis has basically been stipulated in the regulations of the State Administration Institute (LAN) as one of the requirements the implementation of personnel training. ASN Act No. 5 of 2014 has mandated that civilian officials can work with full responsibility and independence on which the need for development of competencies of civil servants. AKD implementation is done with direct assessment through the medium of a spreadsheet, or a questionnaire that was circulated to all employees through staff personnel Batu SKPD respectively. Results of the data obtained AKD training needs that were previously unthinkable to be considered as subject matter training.   Keywords: Implementation, Training Needs Analysis (AKD), employee competence.   Abstrak: Implementasi Analisis Kebutuhan Diklat (AKD) dalam Rangka Pengembangan Kompetensi Aparatur Sipil. Analisis Kebutuhan Diklat merupakan program penyelenggaraan suatu kegiatan dimana berkaitan erat dengan perencanaan diklat. Pemerintah Kota Batu melalui BKD Kota Batu melaksanakan program AKD dengan tujuan agar pelaksanaan diklat dapat tercapai dengan efektif dan tepat sasaran. Target atas keberhasilan pelaksanaan diklat merupakan parameter keberhasilan demi mewujudkan sumber daya aparatur yang kompeten.  Analisis Kebutuhan Diklat pada dasarnya telah tertuang dalam peraturan Lembaga Administrasi Negara (LAN) sebagai salah satu syarat pelaksanaan diklat kepegawaian. Undang-undang ASN nomor 5 tahun 2014 telah mengamanatkan agar aparatur sipil bisa bekerja dengan penuh tanggung jawab dan mandiri yang menjadi dasar perlunya pengembangan kompetensi pegawai negeri sipil. Implementasi AKD dilakukan dengan penjajakan langsung melalui media lembar isian atau kuesioner yang diedarkan kepada seluruh pegawai kota Batu melalui staf kepegawaian SKPD masing-masing. Hasil dari AKD diperoleh data kebutuhan-kebutuhan diklat yang sebelumnya tidak terpikirkan untuk dipertimbangkan sebagai pokok masalah diklat.   Kata kunci: Implementasi, Analisis Kebutuhan Diklat (AKD), kompetensi pegawai.